EXAMINATION OF THE RELATIONSHIP BETWEEN THE AGILITY SKILL AND FATIGUE LEVELS OF SOCCER PLAYERS THROUGH ILLINOIS AND 5-0-5 AGILITY TEST - Mulazimoglu, Olcay; Afyon, Yakup Akif; Agin, Bahtiyar (Acta Scientiae et Intellectus, 2024)
In this study, it is aimed to examine the agility skills of football players in case of fatigue. 12 male amateur trained soccer players (age=23.33±1.83 years; experience= 12.00±2.00 years) were voluntarily participated in this research. The Illinois Agility Test and 5-0-5 Agility Test, which are often used in the measurement of the agility skills, were first performed by the players without any physical strain (pre-test). The agility tests (post-test) were immediately performed after the Yo-Yo Intermittent Recovery Test 1 (YYIRT1), which caused fatigue in the players, was performed by the player. The resting, maximal, pre- and post-test heart rate frequencies of the players were recorded via a heart rate monitor (Polar RS800CX, Electro Oy, Kempele, Finland). Pearson correlation analysis and difference test (Paired-Sample t test) were used for pre-test and post-test agility test scores and heart rate values which showed normal distribution by normality test (Shapiro-Wilk.) and the results were evaluated at the level of significance 0.05. It was determined that the maximal heart rate was 90.13 ± 1.49% after YYIRT1 test. The pre-test and post-test scores of the Illinois and 5-0-5 agility tests showed a significant positive correlation between intra- and intergroup groups (p<0,05). While it was found that there was statistically significant difference between the pre- and post-test scores of 5-0-5 agility test (t=-3.74; p<0,01) in favour of the pre-test, it was found that there was no significant difference between the pre- and post-test scores of the values of the Illinois post-test (t= -0.147; p>0.05). Although significant relationship between the two tests confirms that these tests can be used to measure agility skill based on the findings of the study, it can be inferred that these tests measure the different properties of the agility skill because of different effects of fatigue on these agility tests.